Parental Engagement in Emotional Regulation: A Case Study of Kindergarten Children in Yogyakarta - Muthmainah, Muthmainah; Eka Sapti Cahya Ningrum; Martha Christianti (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2023)
This research aimed to investigate the role of parents in managing their kindergarten-aged children's negative emotions. Utilizing a descriptive, qualitative case study approach, the study was conducted in Yogyakarta, involving six parents, six teachers, and three children. Data collection comprised in-depth interviews and non-participant observation, analyzed using an interactive model by Miles et al. (2014). The results revealed that parents act as supporters, teachers, students, counselors, and guardians in their children's emotional development. Case studies of children, namely AD, NK, and AT, highlighted strategies like modeling positive behavior, teaching problem-solving and dynamic management, and providing comfort. Parents should enhance their knowledge and expertise and motivate their children to learn practical negative emotion management skills. Negative emotion management enhances kindergarten children’s well-being and aids in their adjustment to their surroundings. The implications of these findings emphasize the importance of a supportive, responsive, and involved parenting approach, particularly in emotional development during early childhood. This aligns with Bandura's observational learning theory and resonates with findings from Hornby and Epstein on parental education and involvement. However, the study acknowledges limitations, including its small sample size and qualitative focus, suggesting the need for further research with broader, more diverse samples and quantitative methods. Overall, this study underscores the significant impact of parental involvement on children's emotional resilience and intelligence, highlighting the need for effective parental guidance programs and enhanced teacher-parent collaboration in early childhood education settings.